Comparison of 20% mannitol and 3% hypertonic saline on intracranial pressure and systemic hemodynamics. (August 2017) - Sokhal, Navdeep; Rath, Girija Prasad; Chaturvedi, Arvind; Singh, Manmohan; Dash, Hari Hara
Highlights: Mannitol and hypertonic saline are common hyperosmotic agents used for intraoperative brain relaxation. Changes in ICP and systemic hemodynamics were compared after infusion of equiosmolar solutions of both agents. Both agents in equiosmolar concentrations produced comparable effects on ICP reduction, brain relaxation, and systemic hemodynamics. Abstract: Mannitol and hypertonic saline (HS) are most commonly used hyperosmotic agents for intraoperative brain relaxation. We compared the changes in ICP and systemic hemodynamics after infusion of equiosmolar solutions of both agents in patients undergoing craniotomy for supratentorial tumors. Forty enrolled adults underwent a standard anesthetic induction. Apart from routine monitoring parameters, subdural ICP with Codmann catheter and cardiac indices by Vigileo monitor, were recorded. The patients were randomized to receive equiosmolar solutions of either 20% mannitol (5 ml/kg) or 3% HS (5.35 ml/kg) for brain relaxation. The time of placement of ICP catheter was marked as T 0 and baseline ICP and systemic hemodynamic variables were noted; it was followed by recording of the same parameters every 5 min till 45 min (Study Period). After the completion of study period, brain relaxation score as assessed by the neurosurgeon was recorded. Arterial blood gas (ABG) was analysed every 30 min starting from T 0 upto one and half hours ( T 90 ), and values of various parameters were recorded. Data was analysed using appropriate statistical methods. Both mannitol and HS significantly reduced the ICP; the values were comparable in between the two groups at most of the times. The brain relaxation score was comparable in both the groups. Urine output was significantly higher with mannitol. The perioperative complications, overall hospital stay, and Glasgow outcome score at discharge were comparable in between the two groups. To conclude, both mannitol and hypertonic saline in equiosmolar concentrations produced comparable effects on ICP reduction, brain relaxation, and systemic hemodynamics.